Prácticas de responsabilidad social interna y la satisfacción laboral de los trabajadores de Sesuveca del Perú S.A.C. 2022 - Esquivel Chuquimango, Eliana Lucero (2023)
The present work was carried out in order to determine the relationship between internal social responsibility practices on the job satisfaction of the workers of the company Sesuveca del Perú S.A.C. Trujillo 2022. The problem was: What is the relationship between internal social responsibility practices and job satisfaction of the workers of the company Sesuveca del Perú S.A.C.? The hypothesis was: Internal social responsibility practices are directly related to the job satisfaction of the workers of the company Sesuveca del Perú S.A.C. The design was non-experimental of a cross-correlational type, the survey technique was used, which had the questionnaire as an instrument. The methods used were: descriptive, inductive and analytical. The population and sample were 34 workers from the company Sesuveca of Peru S.A.C. The result is that the company in question carries out internal responsibility practices, which has satisfied the majority of workers when carrying out their work, due to the good working environment, flexible hours, training, good relations with their colleagues and immediate boss, in other aspects. It was concluded that the practices of internal social responsibility have a direct and significant relationship in the job satisfaction of the workers of the company Sesuveca del Perú S.A.C. Trujillo 2022.